1) ¬b∧(a→b)∧a=¬b∧(¬a∨b)∧a=(¬b∧¬a∨¬b∧b)∧a=(¬b∧¬a∨0)∧a=¬b∧¬a∧a=¬b∧(¬a∧a)=¬b∧0=0
We have a contradiction.
Let's build a truth table for the formula to show that it is a contradiction:
Answer: contradiction
2) (a→b)↔(¬a∨b)=(¬a∨b)↔(¬a∨b)=1
We have a tautology.
Let's build a truth table for the formula to show that it is a tautology:
Answer: tautology
3) ((p→q)→r)∧(¬q↔(p∧¬q))=(¬(p→q)∨r)∧(¬q→(p∧¬q))∧((p∧¬q)→¬q)=(¬(¬p∨q)∨r)∧(q∨(p∧¬q))∧(¬(p∧¬q)∨¬q)=(p∧¬q∨r)∧(q∨(p∧¬q))∧(¬p∨q∨¬q)=((p∧¬q)∨(r∧q))∧(¬p∨1)=((p∧¬q)∨(r∧q))∧1=(p∧¬q)∨(r∧q)
Let's build a truth table for the given f1=((p→q)→r)∧(¬q↔(p∧¬q)) and obtained f2=(p∧¬q)∨(r∧q) formulas:
Thus, the formula is found correctly
Answer: (p∧¬q)∨(r∧q)
4) ¬a∧(b⊕c)∧(¬b∨c)=¬a∧(b↔c)∧(¬b∨c)=¬a∧((b→c)∧(c→b))∧(¬b∨c)=¬a∧((b→c)∨(c→b))∧(¬b∨c)=¬a∧((¬b∨c)∨(¬c∨b))∧(¬b∨c)=¬a∧((b∧¬c)∨(c∧¬b))∧(¬b∨c)=¬a∧(b∨c)∧(¬c∨c)∧(b∨¬b)∧(¬c∨¬b)∧(¬b∨c)=¬a∧(b∨c)∧1∧1∧(¬c∨¬b)∧(¬b∨c)=¬a∧(b∨c)∧(¬c∨¬b)∧(¬b∨c)=¬a∧(b∨c)∧¬b∧(¬c∨c)=¬a∧(b∨c)∧¬b=(¬a∧b∨¬a∧c)∧¬b=¬a∧b∧¬b∨¬a∧c∧¬b=0∨¬a∧c∧¬b=¬a∧c∧¬b
Let's build a truth table for the given and obtained formulas:
Thus, the formula is found correctly.
Answer: ¬a∧c∧¬b